Cinética da glicemia e lactatemia em diabéticos tipo 2 durante e após exercício aeróbio realizado em diferentes intensidades - Carvalho, Wolysson Hiyane de (2006)
With the purpose of analyzing the blood glucose responses during and after exercise performed at 90 and 110% of anaerobic threshold (AT) and compare the intensity of lactate threshold (LT) with the intensity of delta lactate (DL), 14 type-2 diabetic patients (DM2) (60±11 years; 79±15 Kg; 162±6.5 cm) performed an incremental test (IT) on cycle ergometer. After the IT for AT identification, participants to three experimental sessions on different days: a 20 min of cycling either at 90 or 110% of AT (with the identification of DL) and a control session (CON). Blood glucose was measured at rest, 10 and 20th min of exercise or control condition, as well as at each 15 min during a 2 hour post-exercise recovery period (Rec). Test t-student no identified differences significant between LT and DL of variation 0. The One Way ANOVA did not identify significant differences in blood glucose between the 90 and 110% AT session. Both exercise intensities induced a significant decrease in blood glucose compared to CON, a significant decrease was observed at the 20th min of exercise (-41 + 15 mg.dl-1), and at the 15th min (-48 + 21 mg.dl-1) and 60th min of Rec from the 90% of AT session. It was also observed a significant decrease at 10 and 20 min of exercise and at 15th, 30th, 45th, 60th and 90th min of Rec from the session at 110% of AT. The exercise performed at a higher intensity (110% AT) resulted in a higher hypoglicemiant effect and may be an alternative of exercise intensity to better control the blood glucose for type 2 diabetics well no have cardiovascular complications or other restrictions to exercise performed above the AT. The DL of variation 0 can be used as a submaximum method to identify of the LT.